NANOTECHNOLOGY AN EMERGING NEW TECHNOLOGY FOR INDONESIA PART I. NANOTECHNOLOGY IN GENERAL - Ratnawati Ratnawati; anggoro D.D. Anggoro; G.A. Mansoori G.A. Mansoori (Reaktor, 2006)
Nanotechnology is shortly defined as the ability to build micro and macro material and product with atomic precistion. Feynman is considered to be the scientist who put a strong foundation for the development of nanotechnology with his phenomenal speech in 1959 entitled "There's Plenty of Room at the Bottom - An invitation to enter a new field of physics." The invention of scanning tunneling microscope, followed by atomic force microscope, has enabled the world to see atoms and nolecules and opened more possibility for the scientists to develop nanotechnology. Other breakthough in nanotechnology is the discoveries of fullerene, carbon nanotube and diamondoids. Nanotechnology has found various fields of application, such as in biomedical , materials, aerospace, surface science and energy, to name a few, lead by the united States, Europe, and Japan, The technology brings benefits as well as risks to human life. Some of the risks are potentially global in scope. It is why a single, trustworthy, international administration holding controls on the technologyis is urgently needed.